2017
DOI: 10.3390/ma10070710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Core-shell Ceria/Poly(Vinylpyrrolidone) (PVP) Nanoparticles Incorporated in Polymer Films and Their Optical Properties (2): Increasing the Refractive Index

Abstract: We investigated the preparation of well-dispersed core-shell ceria-poly(vinylpyrrolidone) (PVP) nanoparticles with an average particle size of around 20 nm which were used to produce a hybrid film with a polymer coating of dipentaerythritol hexaacrylate (DPHA). We obtained good dispersion of the nanoparticles in a mixed solvent of 48% 1-methoxy-2-propanol (MP), 32% 3-methoxy-3-methyl-1-butanol (MMB), and 20% methyl i-butyl ketone (MIBK). An ink of the polymer coating consisting of 68.7 wt% nanoparticles and 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Polyvinylpyrrolidone (PVP) has attracted much attention due to its impressive properties, such as its biocompatibility, nontoxicity, solubility in water and many organic solvents, pH stability, affinity to complex both hydrophobic and hydrophilic substances, and status as chemically inert in physiological reactions [34]. The use of PVP opens additional opportunities for the synthesis [35] and stabilization of metal nanopowders [36,37], modification of various substances [38,39] and materials [40,41], improvement of modern technologies [42,43], production of new functional materials [44,45], and the respective expansion of their fields of use [10,46].…”
Section: Introductionmentioning
confidence: 99%
“…Polyvinylpyrrolidone (PVP) has attracted much attention due to its impressive properties, such as its biocompatibility, nontoxicity, solubility in water and many organic solvents, pH stability, affinity to complex both hydrophobic and hydrophilic substances, and status as chemically inert in physiological reactions [34]. The use of PVP opens additional opportunities for the synthesis [35] and stabilization of metal nanopowders [36,37], modification of various substances [38,39] and materials [40,41], improvement of modern technologies [42,43], production of new functional materials [44,45], and the respective expansion of their fields of use [10,46].…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve this problem, highly dispersible BT nanoparticles were prepared with polyvinylpyrrolidone (PVP) by the low temperatures synthesis (LTS) and hydrothermal (HT) process, referred to as LBT-PVP and HBT-PVP respectively, as reported in our previous paper [ 21 , 22 ]. The nanoparticles prepared by these methods can be dispersed as suspension in a coating slurry, and with these particles thin film layers can be prepared easily and quickly by a bar coating process as Itoh et al reported [ 23 ]. This process does not require high-temperature treatment and the performance of the film depends on the crystalline phase of the powder.…”
Section: Introductionmentioning
confidence: 99%